Time for a Change. Issue 1 (3rd April 2018) - Lenz, Gabriel
ABSTRACT: Political scientists should put aside questions about whether voters are rational or irrational, informed or uninformed, and questions about how flawed democracy is. Although they are interesting, these questions are secondary. Answering them in no way helps people—it does not help them with their violent neighborhoods, their declining incomes, their flooded homes, or their dying crops. Instead, researchers should focus on the first-order question of how to improve democratic accountability.